″A Description of Professional Functions of an Engineer-Pedagogue Specializing in Transport″ - Ivanova, A. V. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the specifics of engineering-pedagogical activity that consists of organic combination of engineering and pedagogical activity functions. Basing on the analysis of some scientific works, professional functions of an engineering industry representative are defined in the paper. The article characterizes certain functions of pedagogical activity in the engineeringpedagogical sphere and specifies features of vocational education aimed at training a leading constituent part of the workforce, i.e. skilled employees for all industries of material and nonmaterial production as well as for any other types of production activity. Taking into consideration the essence of professional competence of a future motor transport engineer, the meaning and role of an engineer-pedagogue are clarified in terms of vocational training of the former. The analysis of scientific works, which was conducted to discover functions of engineers-pedagogues of different specializations, allowed the author to single out and characterize the following professional duties of an engineer-pedagogue specializing in transport: design-engineering, organizational-administrative, technological, educational, and scientific-research. Each of the defined functions envisages the presence of special knowledge and skills necessary for future professionals which are supposed to be developed in the process of vocational training in higher educational institutions. Defining the functions will improve the quality of the search for ways of increasing the efficiency of vocational training of an engineer-pedagogue specializing in transport for performing these functions.